The Influence of Management Accounting Information Systems and Performance Measurement System on Managerial Performance - Siska Septiani; Gun Gunawan Rachman (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2021)
This study aims to examine the effect of management accounting information systems and performance measurement systems pn managerial performance. Management accounting information system is a process of the activities of an information system so that the resulting information can help managers to make decisions. Furthemore, the performance measurement system is a measurement that is used to monitor employee performance. Management accounting information systems and performance measurement systems can increase or decrease managerial performance in companies. The object of this research is PT. Sangkuriang Jaya Abadi located in Antapani, Bandung. This study uses a survey method with the number of respondents employees and managers. The data used in this study is primary data and uses a data collection method using a questionnaire. The results of the study are 1) Management accounting information system has an effect on managerial performance.2) The performance measurement system has an effect on managerial performance.